A perspective on bioethanol production from biomass as alternative fuel for spark ignition engine - Sebayang A.H.; Masjuki H.H.; Ong H.C.; Dharma S.; Silitonga A.S.; Mahlia T.M.I.; Aditiya H.B. (Royal Society of Chemistry, 2023)
Alternative fuels; Carbon; Carbon dioxide; Engines; Ethanol; Fossil fuels; Fuels; Gasoline; Global warming; Greenhouse gases; Bio-ethanol production; Biofuel production; Biomass feedstock; Carbon dioxide emissions; Engine performance; Gasoline blends; Lignocellulosic material; Particulate Matter; Bioethanol